KEBERADAAN KOMUNITAS GAMELAN KANDANG AYAM DI HELVETIA MEDAN - Dedek Riyando (Grenek: Jurnal Seni Musik, 2013)
Based on the research conducted, it can be known background of gamelan community was founded by Mr. H Kasto Semon in 2009 which is located at Jalan Sejahtera No. 354 Helvetia aims to recruit / collecting native Javanese people from Wonogiri to familiarize and develop a culture of Java. Public response about Kandang Ayam gamelan community in Medan is very good, starting from where people can be interested in gamelan music, who had no idea of traditional Javanese music be known in the presence of gamelan music performances. The songs are sung Kandang Ayam gamelan community in Helvetia Medan is rhythmic songs langgam seperti caping gunung, nyidam sari, ali-ali, sri kuning, yeng ing tawang, gambang suling, jenang gulo dan jangkrik genggong. is rhythmic songs ladrang seperti selamat, sri widodo, kijeng nireng, pengantin, Liwung, wahyu dan wilujeng.